Pengaruh Pendidikan, Paritas, dan Pemanfaatan BPJS dengan Pemilihan Metode Kontrasepsi pada Akseptor KB di Puskesmas X Kota Depok - Krisnafi, Zhafira Alya Putri; Damayanti, Rita (Master of Epidemiology, Faculty of Public Health, Diponegoro University, Indonesia, 2026)
Background: The use of Long-Acting Reversible Contraception (LARC) in Indonesia is still far from the national target. A similar thing was observed at Community Health Center “X” Depok City where LARC use remained low in 2023 (22.75%). Education, parity, and BPJS utilization are factors that can influence the low use of MKJP. This study aims to analyze the relationship between these three factors and contraceptive choice at Community Health Center “X” Depok City.Methods: This quantitative study employed a cross-sectional design. This study uses secondary data from family planning register records at Community Health Center “X” Depok City in 2024 with a total of 247 family planning acceptors. Data were analyzed using univariate, bivariate, and multivariate methods.Result: The distribution of contraceptive use showed that 50.6% of acceptors used non-LARC methods, while 49.4% used LARC. Multivariate analysis indicated a significant association between parity and LARC use (p = 0.002; OR = 1.9; CI = 1.2–2.9). In contrast, education (p = 0.956; OR = 0.9; CI = 0.6–1.5) and BPJS utilization (p = 0.678; OR = 1.1; CI = 0.7–1.7) were not significantly associated with LARC use.Conclusion: Parity is the most influential factor in the choice of contraceptive methods among family planning acceptors at Community Health Center “X” Depok City in 2024. These findings imply the importance of improving outreach and the quality of services provided by healthcare workers to building public trust in the use of LARC and BPJS.